Phylogenetic comparative analysis of functional morphology sheds light on the evolution of seasonal migration in nightingale-thrushes (Turdidae: Catharus) - Matthew R. Halley; Therese A. Catanach; John Klicka; Jason D. Weckstein (Scientific Reports)
Abstract This study investigates the evolution of locomotory morphology and migratory behavior in nightingale-thrushes (genus Catharus), a clade of songbirds with diverse migratory strategies. With large datasets of molecular and morphometric characters, we resolve phylogenetic relationships, identify and model migration-related morphological characters, and estimate ancestral states of those characters to infer evolutionary transitions in the migratory phenotype. While acknowledging that unknown factors (e.g., differential extinction) may confound interpretation, our results suggest that (1) migratory behavior and its functional morphology are fundamentally linked; (2) short-distance or elevational migration (not long-distance) was the ancestral state of Catharus; (3) short-distance migration was the evolutionary precursor of long-distance migration; and (4) the short-distance migrant, Hermit Thrush (C. guttatus), may be in relative phenotypic (ecological) stasis. This potentially explains the ecological incumbency of C. guttatus in temperate North America during winter, and offers a new framework for interpreting the evolutionary sequence that produced long-distance migration in this model system.